Photocatalytic actives of PVDF/TiO2 produced by solution blow spinning with silver nanoparticles adsorbed on the surface - de Paula, Fernando; Padovani, Guilherme; O. Sanches, Alex; F. Malmonge, Luiz (International Journal of Research Science and Management, 2023)
An efficient method for manufacturing nano-submicron PVDF/TiO2 fibers was developed by solution blow spinning and subsequent incorporation of silver nanoparticles. In this work, we tried to use Ag particles prepared by the reduction of AgNO3 with NaBH4 in solution to increase the photocatalytic activity of the membrane; the nanoparticles remained on the surface of the PVDF/TiO2 fibers after the bath. The SEM image shows transparent fibers with Ag nanoparticles coated along the entire fiber. XRD revealed the anatase and rutile phases and the metallic form of Ag, and XPS confirmed Ti and O as well as Ag. In the presence of silver nanoparticles, fibers showed a significant increase in dye degradation, and excess silver was also observed to decrease photocatalytic activity. Furthermore, the fibers show promise as antibacterial agents.